Tuning the Mechanical Properties of Shape Memory Metallic Glass Composites with Brick and Mortar Designs. (September 2020) - Yuan, Suyue; Song, Xinxiang; Branicio, Paulo S.
Abstract: We use molecular dynamics simulations to characterize the tensile deformation and failure of shape memory alloy-bulk metallic glass composites (BMGCs). As the failure in BMGCs shifts from the MG matrix to the second phase different strategies are required to further improve their mechanical properties. Results show that a staggered brick BMGC displays enhanced ductility with mild strength loss following a homogeneously distributed plasticity. This demonstrates that judiciously designed BMGCs can effectively synergize the mechanical properties of metallic glasses and shape memory alloys by effectively distributing stress and preventing the generation of critical shear bands and premature failure while preserving strength. Graphical Abstract: Image, graphical abstract